Management - Daft, Richard L (Dryden Press series in management., 2000)
The sixth edition of this market leading text continues to raise the standard through its cutting-edge presentation of managerial thought, carefully developed applications, and innovative technology components. Richard Daft seamlessly integrates the new workplace with traditional management concepts to show what influences and guides managerial action in today's organizations. To illustrate the conceptual material and engage the reader, Daft includes diverse examples, exercises, applications in every chapter. Through each edition, Management has continued to build an outstanding reputation with instructors for its quality, topic selection, applications, and authorship.